Comparison of Cross-linked and Non-Cross-linked Acellular Porcine Dermal Scaffolds for Long-term Full-Thickness Hernia Repair in a Small Animal Model - Měšťák, Ondřej; Špůrková, Zuzana; Benková, Kamila; Veselý, P; Hromádková, Veronika; Miletín, Jakub; Juzek, Robert; Měšťák, Jan; Molitor, Martin; Sukop, Andrej (Eplasty, 2014)
Background: This study compared the strength of incorporation and biocompatibility of 2 porcine-derived grafts (cross-linked and non-cross-linked) in a rat hernia model. Methods: A standardized 2 × 4 cm(2) fascial defect was created in 30 Wistar rats and repaired with either a cross-linked or a non-cross-linked graft. The rats were killed 3, 6, and 12 months later. The strength of incorporation, vascularization, cellular invasion, foreign body reaction, and capsule formation were evaluated. Results: Both graft materials showed cellular ingrowth and neovascularization by 3 months postimplantation. The average level of cellularization was significantly higher in the non-cross-linked grafts than in the cross-linked grafts at 6 months (2 vs 1; P = .029). Vascularization was significantly higher in the non-cross-linked grafts than in the cross-linked grafts at 6 months postimplantation (2 vs 1; P = .029) and insignificant at 3 months (2 vs 1.75; P = .311) and 12 months (1 vs 0.67; P = 1). The maximum load and breaking strength of both biomaterials increased during the study period. Overall, the strength of incorporation of the non-cross-linked grafts increased from 3 months (0.75 MPa) to 12 months (3.06 MPa) postimplantation. The strength of incorporation of the cross-linked grafts also increased from 3 months (0.59 MPa) to 12 months (1.58 MPa) postimplantation. Conclusions: The results of our study suggest that non-cross-linked grafts may be slightly more biocompatible and allow a more rapid and higher degree of cellular penetration and vascularization, resulting in stronger attachment to the tissues.